Open-structured silica network based on silane-terminated telechelic polybutadiene for electric vehicle tires - Kiwon Lim; Seung Jae Hong; Hyungjae Lee; Jaehyun Jung; Kihyun Kim; Park, Jong Hyuk; Joona Bang (Elsevier BV, 2024)
The shift towards electric vehicles (EVs) is essential for a sustainable future. Tire manufacturers face challenges including accommodating extra weight, managing instant torque, reducing noise, and improving driving range. Meeting these demands involves substantially reducing the rolling resistance of tire tread composites while simultaneously enhancing their mechanical stiffness and wear resistance. To overcome these issues, an open-structured silica network based on silane-terminated liquid-like telechelic polybutadienes was introduced into rubber composites. This unique network consists of silica aggregates that are chemically bound together, but exhibit physical separation, enabling rubber chains to permeate. The infiltrated polymer chains were tightly constrained by the network, resulting in a notable increase in the crosslink density and mechanical strength of the composite. Furthermore, the tan δ values at 60 °C showed a notable decrease as a result of diminished interparticle friction caused by isolated silica structures and reduced mobility of polymer chains within the network. These findings provide the tire industry with crucial insights for the development of energy-efficient and durable tires for EVs. By addressing these specific requirements of EVs, our study paves the way for more sustainable tires and contributes to the broader adoption of EVs in a sustainable future.